Self-assembled monolayer facilitates epithelial-mesenchymal interactions mimicking odontogenesis - Muni, Tanvi (Connect Tissue Res, 2014)
Cell-cell interactions are vital for embryonic organ development and normal function of differentiated cells and tissues. In this study we have developed a self-assembled monolayer-based co-culture system to study tooth morphogenesis. Specifically, we designed a 2-D microenvironment present in the dental tissue by creating a well-structured, laterally organized epithelial and mesenchymal cell co-culture system by patterning the cell-attachment substrate. Chemical modifications were used to develop tunable surface patterns to facilitate epithelial-mesenchymal interactions mimicking the developing tooth. Such a design promoted interactions between monolayer’s of the 2 cell types and provided signaling cues that resulted in cellular differentiation and mineralized matrix formation. Gene expression analysis showed that these co-cultures mimicked in-vivo conditions than monolayer cultures of a single cell type.